Implementasi Perwako Bukittinggi Nomor 12 Tahun 2022 Tentang Mekanisme Pengelolaan Pengaduan Pelayanan Masyarakat Secara Elektronik Ditinjau Dari Perspektif Siyasah Tanfidziyah - Laila Rahmi (KIPS Institute, 2025)
Problems in the management of public service complaints have become an open secret among the public, one of which is the slow follow-up from the government in handling complaints filed by the public. In addition, along with the changing times, the environment has become a dynamic society and indirectly requires the government to innovate. the purpose of this study is to determine the extent of the implementation of Perwako Bukittinggi Number 12 of 2022 concerning the Mechanism for Managing Electronic Public Service Complaints and how from the point of view of Siyasah Tanfidziyah towards the implementation of public service policies in Bukittinggi City. The research method uses Field Research with a qualitative approach and the number of informants is 7 people. Techniques and data collection are done through observation, interviews, and documentation. To determine the success rate of policy implementation, researchers used the implementation theory put forward by George C Edward III. The results showed that 1) the level of communication needs to be improved because if through digital media it does not reach all circles of Bukittinggi City society 2) the resource aspect in terms of facilities has been fulfilled but in terms of human resources it has not run optimally because there is no time limit in the handling process making government officials delay action on incoming reports 3) for disposition, it has gone well 4) aspects of the bureaucratic structure, the Communication and Information Office has implemented the applicable SOP. Then in the view of Siyasah Tanfidziyah it is still not running effectively because there are still articles in the Perwako that have not been implemented. Policy implementation has not been carried out optimally because seen from the resource indicator, in the process there are still reports that have not been processed by government officials. Then on the communication indicator, Diskominfo moved too quickly to digital media without taking into account the number of people who follow Diskominfo's social media accounts.